CORPORATE GOVERNANCE DAN ETNISITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Trudy Maryona Nussy (Jurnal Keuangan dan Perbankan, 2013)
The objective of research was to examine the effect of corporate governance and ethnicity on the disclosure ofCorporate Social Responsibility (CSR). Corporate governance mechanisms used in this research were managerialownership, institutional ownership, independent commissioner, and audit committee. Research was conductedagainst the companies listed in Indonesia Stock Exchange in the period of 2005 and 2011. Samplingtechnique was purposive sampling. Hypothesis testing was conducted by independent sample t-test and multipleregressions. Test and analysis were carried out separately in 2005 and 2011. The result of researchindicated that there was a difference in the CSR disclosure rate. The use of CSR in Indonesia in 2011 washigher than that in 2005. The managerial ownership and the institutional ownership influenced CSR disclosurein 2005, while independent commissioner, audit committee and ethnicity did not influence CSR disclosurein 2005. The disclosure of CSR in 2011 was affected by institutional ownership, independent ownershipand audit committee. The managerial ownership and ethnicity did not influence CSR disclosure in this year.